A First Order q-Difference System for the BC₁-Type Jackson Integral and Its Applications - Ito, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We present an explicit expression for the q-difference system, which the BC1-type Jackson integral (q-series) satisfies, as first order simultaneous q-difference equations with a concrete basis. As an application, we give a simple proof for the hypergeometric summation formula introduced by Gustafson and the product formula of the q-integral introduced by Nassrallah-Rahman and Gustafson.